ANALISIS STRUKTUR PASAR, EFISIENSI DAN PROFITABILITAS: STUDI KASUS PERBANKAN SYARIAH 2010-2015 - Kristi, Acknes Marta (Jurnal Ilmiah Mahasiswa FEB, 2016)
This study aims to determine the market structure , efficiency and profitability of Islamic banking industry in Indonesia. The data in this resesarch is derived from the quarterlyÂ  reports of the financial of banks in 2010-2015. The methods used in this research are Data Envelopment Analysis (DEA) and Â panel regression analysis. The results of this research are market concentration has a positive effect on the level of profitability of a bank. In additional discoveries of the control variables (NPF and BOPO) have negative effect on the level of profitability.Kata kunci: Market structure, concentration, profitability